The Therapeutic Potential and Limitations of Ketones in Traumatic Brain Injury - Daines, Savannah Anne (Frontiers in Neurology, 2021)
Traumatic brain injury (TBI) represents a significant health crisis. To date, no FDA approved pharmacotherapies are available to prevent the neurological deficits caused by TBI. As an alternative to pharmacotherapy treatment of TBI, ketones could be used as a metabolically based therapeutic strategy. Ketones can help combat post-traumatic cerebral energy deficits while also reducing inflammation, oxidative stress, and neurodegeneration. Experimental models of TBI suggest that administering ketones to TBI patients may provide significant benefits to improve recovery. However, studies evaluating the effectiveness of ketones in human TBI are limited. Unanswered questions remain about age- and sex-dependent factors, the optimal timing and duration of ketone supplementation, and the optimal levels of circulating and cerebral ketones. Further research and improvements in metabolic monitoring technology are also needed to determine if ketone supplementation can improve TBI recovery outcomes in humans.